Safeguarding Regional Government Assets (Barang Milik Daerah) in Teluk Bintuni Regency: A SWOT-Based Strategy for Administration and Inventory Management - Mery Maria Mahdalena Saday; Meinarni Asnawi; Syaikhul Falah; Balthazar Kambuaya; Paulus K. Allo Layuk; Quincy F. Kambuaya (Manunggal Halim Jaya, 2026)
This study aims to analyze the administration and inventory management of Regional Government Assets (Barang Milik Daerah/BMD) in Teluk Bintuni Regency and to formulate effective safeguarding strategies. The research employs a qualitative descriptive approach involving asset management officials from the Regional Financial and Asset Management Agency (BPKAD), Regional Secretariat (SETDA), and Regional Apparatus Organizations (OPDs). Data were analyzed using SWOT analysis supported by IFAS (Internal Factor Analysis Summary) and EFAS (External Factor Analysis Summary) matrices to evaluate internal strengths–weaknesses and external opportunities–threats. The findings show that BMD management is in a relatively strong internal condition (IFAS score = 3.29, indicating above-average internal capacity), supported by regulatory frameworks, the use of information systems, leadership commitment, and trained personnel. However, weaknesses persist, including inconsistent data updates, weak internal supervision, and uneven human resource capacity, which may affect governance quality. From an external perspective, opportunities such as digitalization initiatives and increased accountability demands can be leveraged to improve asset management. The SWOT analysis places the strategy in Quadrant I (growth-oriented strategy), indicating that strengths can be optimized to capture available opportunities. Recommended strategies include strengthening regulations, accelerating digitalization of asset systems, improving human resource capacity through collaboration, standardizing data updating mechanisms, and enhancing cross-OPD supervision. Practically, these findings provide policy-relevant recommendations for local governments to improve transparency, accountability, and efficiency in asset management. The implementation of these strategies is expected to support more sustainable and accountable BMD governance, particularly in developing regional contexts.